(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Pituitary adenomas (PA) are benign neoplasms that arise from adenohypophysis; they are most common skull base tumors, and account for 12% to15% of all intracranial tumors. In PA with supraparasellar extension, a tumor grows upward, causing chiasmal and lateral cavernous sinus compression. Because prolonged compression of the optic nerve/chiasm complex results in the development of primary descending ONA in 31% to 72% of patients, leading to blindness in 3.5% to 16% of patients, the issue is worthy of attention. Purpose: To investigate neuro-ophthalmological symptoms in pituitary adenomas with a supraparasellar extension before and after treatment. Materials and Methods: This retrospective study included the records of 107 patients who received treatment for pituitary adenomas with a supraparasellar extension at the Romodanov Institute during 2017 to 2018. The main group included 49 patients (98 eyes) who had visual impairments and/or visual field deficits. Patients underwent clinical and neurological, eye and otoneurological examination (including neuroimaging studies) before and after treatment. Results: Visual impairments with the development of markedly asymmetric chiasmal syndrome were most common in the clinical picture, with a severe visual acuity loss (25.5% of eyes) and significant sensitivity loss (39.8% of eyes) in the more affected eye, mild or moderate visual acuity loss and visual field loss in the less affected eye, and development of primary descending optic nerve atrophy in 36 (73.5%) patients. After treatment, visual acuity restored or improved in 57 (58.2%) eyes, and arithmetic mean of the sensitivity loss, the mean defect (MD), improved in 46 (46.9%) eyes (these improvements were significant, p < 0.05). Conclusion: Pituitary adenomas with supraparasellar extension were characterized by the development of visual and oculomotor impairments, which evidenced the presence of various directions of tumor expansion. Visual impairments with the development of markedly asymmetric chiasmal syndrome were most common in the clinical picture. Mean BCVA improved from 0.51±0.04 at baseline to 0.66±0.03 after treatment, and mean overall visual field sensitivity loss improved from 12.11 ± 0.69 dB at baseline to 8.6 ± 0.7 dB after treatment (both improvements were significant, p < 0.05).